Optimalisasi Faktor Lingkungan terhadap Jumlah Spora Terlepas pada Gelidium sp. - Hariyati, Riche (BULETIN ANATOMI DAN FISIOLOGI dh SELLULA, 2008)
This research was conducted to determine the influence of combined environmental factors on theoptimum number of spores released from Gelidium sp. The research was done at the laboratory ofMarine Science Development in Jepara.The design of the experiment used was split plot design basedon Completely Randomized Design with three factors : light intensity, photoperiod and salinity. Eachtreatment has three replications. As main plot was combination between light intensity and photoperiodwith three levels respectively ( 100 lux ; 500 lux ; 1000 lux ) and photoperiod 14 hours light 10 hoursdark ( 14 : 10 hours ; 16 : 8 hours ; 18 : 6 hours ) sub plot was salinity ( 25 %o ; 30 %o ; 35 %o ). Thecollected data were statistically analyzed with ANOVA, followed by DMRT.The result revealed thatthe treatment gave the significant effect on the spores released. The optimum average number of sporereleased of Gelidium sp. Were the combination of light intensity 500 lux, photoperiod 16 : 8 hours andsalinity 30 %o. There was a positive interaction between these three factors in affecting the sporereleased.